Small Traders' Marketing Strategies and Their Quality of Services on Economic Sustainability during the Covid-19 Pandemic in East Bekasi District, Bekasi - Andrian; Pratiwi Nilasari; Christophorus Indra Wahyu Putra (East Asian Journal of Multidisciplinary Research, 2022)
The Covid-19 pandemic that  covered the world has entered a period of more than two years, and of course greatly affects the current pace of world economic growth. This study aims to find out how much influence small traders have on the sustainability of the economy in the East Bekasi sub-district, Bekasi City throughout the Covid 19 epidemic. The study approach employed is purposive sampling method by taking samples from the population of small traders in the area surrounding the District of East Bekasi, amounting to about 100 people. The data that came in through the questionnaire from them was then processed using the latest version of SPSS. The results of the study show that small traders in this area have a significant quality of service in the economic sustainability during these difficult times.